2005
DOI: 10.2106/jbjs.d.02631
|View full text |Cite
|
Sign up to set email alerts
|

Inferior Patellar Pole Avulsion Fractures: Osteosynthesis Compared with Pole Resection

Abstract: In patients who have sustained an avulsion fracture of the inferior patellar pole, the normal height of the patella can be maintained by preserving the patellar pole. In contrast with pole resection, which requires postoperative immobilization, internal fixation with a basket plate allows for immediate mobilization and early weight-bearing. The present study indicates that internal fixation with use of a basket plate can provide better clinical results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 11 publications
0
57
0
2
Order By: Relevance
“…Veselko et al ,4 have reported good long term results with basket plate osteosynthesis versus patellar ligament repair for inferior pole avulsion patellar fractures. Patellar height is preserved at long term follow-up and mobilization is much faster as contrast with ligament repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Veselko et al ,4 have reported good long term results with basket plate osteosynthesis versus patellar ligament repair for inferior pole avulsion patellar fractures. Patellar height is preserved at long term follow-up and mobilization is much faster as contrast with ligament repair.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional recommendation for displaced comminuted inferior pole fractures is excision of the comminuted pole followed by reattachment of the patellar tendon with transosseous suture. There has been one published study on better outcomes obtained following use of a basket plate to attach the avulsed inferior pole of patella as compared to resection of inferior pole of patella4. To the best of our knowledge there has been no previous published study mentioning the use of suture anchors for fractures of the inferior pole of patella.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Iqbal et al [15] in their comparative study found that reattachment of patella tendon to patella showed better clinical results than open reduction and fixation with tension band wiring and our study results were at par with theirs. Veselko and Kastelec [16] in their study found that basket plate fixation gave better outcome compared to partial patellectomy in the management of comminuted inferior pole patella fractures by retaining inferior pole and earlier mobilization. Basket plate is still not in regular use, not available in India and not an economical option for a country of low socioeconomic status.…”
Section: Discussionmentioning
confidence: 97%
“…2 Fractures among the inferior pole have an added problem, the difficulty of surgical repair due to the small amount of bone tissue available or the comminution of the fracture. 3 Once surgery is performed, these types of fractures present with two battlefields for the orthopedic surgeon.…”
mentioning
confidence: 99%
“…Surgical steel, wire, are the most frequent materials used in most centers, due to their ease of use and access. [2][3][4][5] One step for the improvement of this critical point is the use of more resistant materials such as a titaniummade plate or even high-resistant sutures that avoid the removal. With all these variants, we will be able to observe better indexes of fracture consolidation, and fewer local complications and removal of material.…”
mentioning
confidence: 99%